An overview of the science and art of encapsulated pigments: Preparation, performance and application. (11th January 2022) - Tawiah, Benjamin; Asinyo, Benjamin K.; Frimpong, Charles; Howard, Ebenezer K.; Seidu, Raphael K.
Abstract: A successfully encapsulated pigment requires dispersants, pigment and a dispersion medium to build a thin layer of polymer over individual pigment particles. The stability of encapsulated dispersion is aided by the absorption of stabilising molecules on the surface. The stabilising molecules function by steric hindrance or Coulomb‐repulsion forces, which prevent the encapsulated pigments from advancing too close to each other for attractive forces to cause agglomeration. Unlike flocculation, agglomeration results in a cementitious network structure that is not easily redispersed by shear forces, hence the need for effective dispersion of encapsulated pigment intended for engineering applications. Besides dispersion forces, the quality of pigment dispersion, the pigment particle size, pigment density, viscosity of the dispersion, and the method of producing the pigment microcapsules, also affect the efficiency and the quality of encapsulated pigment dispersions. This article, therefore, provides up‐to‐date information on the various pigment encapsulation methods (with specific emphasis on phase separation, in situ polymerisation, emulsion and mini‐emulsion polymerisation, the sol‐gel method, inclusion complexation and layer‐by‐layer assembly), and also reviews the performance, the evaluation/test methods and applications of encapsulated pigments. This review provides important insight into the science and art of encapsulated pigment preparation for pigment dispersion technologists, researchers and consumers of pigment products in different fields of endeavour.